Framing citizen participation participatory budgeting in France, Germany and the United Kingdom - Röcke, Anja 1978- (Palgrave Macmillan, 2014)
"From its origins in Porto Alegre, Brazil, the diffusion of participatory budgeting to other parts of the world has been met with varying degrees of success despite its label as a product of democratic innovation. Drawing on in-depth empirical and theoretical analysis, this book sheds light on the diffusion dynamics of participatory budgeting and the processes of its framing and adaptation in France, Germany and the United Kingdom. It explores the question of participatory budgeting's national characteristics and potential for realising a more democratic society. Thus, the volume engages in a theoretically innovative and empirically grounded overview and critical assessment of participatory budgeting initiatives in three European countries. The double focus on frames in the diffusion and implementation of single cases and the systematic evaluation of their results offers a deeper understanding of "success factors" and results of participatory budgeting and other institutional processes of citizen participation"..
Keywords: Finanzwirtschaft; Wirtschaftspolitik; Budget process -- Europe -- Citizen participation; Finance, Public -- Europe; Local budgets -- Europe -- Citizen participation; Political planning -- Europe -- Citizen participation; Political particpation -- Europe; Local finance -- Europe; POLITICAL SCIENCE / Political Ideologies / Democracy; POLITICAL SCIENCE / Government / Comparative; POLITICAL SCIENCE / Public Affairs & Administration; POLITICAL SCIENCE / Economic Conditions; POLITICAL SCIENCE / Public Policy / Economic Policy; Europa